1995
DOI: 10.1007/bf00374802
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of phosphatidylinositol kinases by arachidonic acid in rat submandibular gland cells

Abstract: Phosphoinositide kinases were characterized in membrane extracts of rat submandibular gland cells. Both phosphatidylinositol (PI) 4-kinase and phosphatidylinositol-4-phosphate (PI(4)P) 5-kinase phosphorylated endogenous substrates in reactions that were linear for up to 5 min, were activated by Mg2+ and showed maximal activity around neutral pH. PI 4-kinase was stimulated by Triton X-100 at an optimal concentration of 0.22%, but the detergent had an inhibitory effect on PI(4)P 5-kinase. Arachidonic acid (AA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…While the positive effects of AA on LK bg were apparent at micromolar ranges of concentration, previous studies showed that the inhibition of PIkinase and the activation of PLCγ by AA occur at tens and hundreds of micromolar concentrations, respectively [6,15]. Also, the activation of PLCs in human platelets by AA is mediated by the metabolites of cyclooxygenase [29].…”
Section: Mechanisms Of Aa Activation Of Lk Bgmentioning
confidence: 95%
“…While the positive effects of AA on LK bg were apparent at micromolar ranges of concentration, previous studies showed that the inhibition of PIkinase and the activation of PLCγ by AA occur at tens and hundreds of micromolar concentrations, respectively [6,15]. Also, the activation of PLCs in human platelets by AA is mediated by the metabolites of cyclooxygenase [29].…”
Section: Mechanisms Of Aa Activation Of Lk Bgmentioning
confidence: 95%
“…Since myocardial ischemia is accompanied by dramatic increases in the mass of the acylcarnitine pool and since the biologic sequelae of amphiphilic constituents containing unsaturated aliphatic chains can be quite different from their saturated counterparts in some systems [e.g., Okamura and Yamashita (1994), Cao and Hatch (1994), and Chung and Fleming (1995)], we sought to identify the distribution of individual molecular species of long-chain acylcarnitines in ischemic myocardium. Historically, the mass of carnitines in biologic tissues has been quantitated by measuring the carnitine acetyltransferase catalyzed conversion of tissue carnitine to [ 3 H]acetyl carnitine (McGarry & Foster, 1976).…”
mentioning
confidence: 99%